2007
DOI: 10.1016/j.ejcts.2007.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Complete regression of a thymoma to glucocorticoids, commenced for palliation of symptoms

Abstract: A patient is presented with Type B1 thymoma that showed complete regression to oral glucocorticoids commenced for palliation of symptoms. The patient has remained symptom free without radiological recurrence after 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 10 publications
0
21
0
2
Order By: Relevance
“…The overall incidence of thymoma is 0.15 cases per 100,000 individuals and the majority of the patients with thymoma or thymic carcinoma are aged 40-60 years (2,3). The World Health Organisation (WHO) classification is based on histological analysis of epithelial cell atypia and the degree of infiltration of non-neoplastic lymphocytes (4). Although the great majority of these tumors exhibit more conventional histological characteristics, unusual types have also been described, such as sclerosing thymoma (5).…”
Section: Introductionmentioning
confidence: 99%
“…The overall incidence of thymoma is 0.15 cases per 100,000 individuals and the majority of the patients with thymoma or thymic carcinoma are aged 40-60 years (2,3). The World Health Organisation (WHO) classification is based on histological analysis of epithelial cell atypia and the degree of infiltration of non-neoplastic lymphocytes (4). Although the great majority of these tumors exhibit more conventional histological characteristics, unusual types have also been described, such as sclerosing thymoma (5).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports described a significantly better response in type B1 thymoma than in other thymoma subtypes, presumably due to the high content of glucocorticoid-sensitive immature lymphocytes in type B1 thymomas. However, these studies found apoptotic changes not only in lymphocytes but also in the neoplastic thymic epithelial cells [43, 44]. Furthermore, glucocorticoid receptors were identified in cultured human thymic epithelial cells, and it has been shown that low-dose steroids lead to an increased expression of the somatostatin gene in the thymus [30, 45].…”
Section: Discussionmentioning
confidence: 99%
“…En 2003, dix cas seulement avaient été rapportés au Japon [5]. Barratt et al avaient rapporté un cas de régression complète d'une tumeur épithéliale thymique de type B1 chez une patiente de 86 ans, après corticothé-rapie [6]. Ils avaient retrouvé trois autres cas identiques dans la littérature.…”
Section: Discussionunclassified
“…L'évolution spontanément régressive et l'ensemble des éléments cliniques, biologiques et radiologiques avaient autorisé une surveillance rapprochée prolongée. Si le phé-nomène de régression spontanée est rare, il pourrait inciter néanmoins à remettre en question le traitement chirurgical d'emblée lorsqu'une diminution de diamètre est observée sur deux scanners successifs et à envisager la surveillance clinique et radiologique comme une alternative chez des patients très sélectionnés [6]. L'exérèse chirurgicale reste le traitement de référence des tumeurs épithéliales thymiques, mais il paraît cependant légitime de reconsidérer l'indication chirurgicale en cas de régression de la lésion et de la réévaluer constamment en fonction de la cinétique de celle-ci.…”
Section: Discussionunclassified